LITERATUR REVIEW: PEMANFAATAN WORDWALL DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA SEKOLAH DASAR - Azizah Rozianita; Joko Sutarto; Mintasih Arbani; Decky Avrilianda; Bambang Subali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education in the digital era has undergone significant transformation. This is due to the use of technology in education. Elementary School, as the core of the formal education system, is very important to incorporate technology into the learning process. Technology has great potential to enhance children's learning experiences, provide people with greater access to learning resources, and optimize teachers' instruction. The purpose of this research is to determine the effectiveness of using Wordwall to help students solve story problems related to single-digit division. This has been demonstrated by many studies and literature. This research was conducted through a literature review, which combines several studies on the same topic into a new topic. The use of Wordwall in learning at elementary schools, based on the literature review. One of its main advantages is the technology's ability to make learning more interactive and engaging for students. However, there is a drawback, which is that students do not have equal access to technology.If students do not have electronic devices or internet connections, they may fall behind in the online learning process, which reduces their opportunities to learn.